FDG-PET/CT Incidental Detection of Cancer in Patients Investigated for Infective Endocarditis - Gouriet, Frédérique; Tissot-Dupont, Hervé; Casalta, Jean-Paul; Hubert, Sandrine; Cammilleri, Serge; Riberi, Alberto; Lepidi, Hubert; Habib, Gilbert; Raoult, Didier (Frontiers in Medicine, 2020)
Abstract: Background: Fluoro Desoxy Glucose PET/CT is an imaging technique largely used in the management of Infective endocarditis and in the detection and staging of cancer. We evaluate our experience of incidental cancer detection by PET/CT during IE investigations and follow-up. Methods and findings: Between 2009 and 2018, our center, which includes an “endocarditis team”, managed 750 patients with IE in a prospective cohort. PET/CT became available in 2011, and was performed in 451 patients. Incidental diagnosis of cancer by PET/CT was observed in 36 patients and confirmed in 34 of them (7.5%) (Colorectal n=17, lung n=7, lymphoma n=2, melanoma n=2, ovarian n=2, prostate n=1, bladder n=1, Ear Nose & Throat n=1, brain n=1). A significant association has been found between colorectal cancer and Streptococcus gallolyticus and/or Enterococcus faecalis (12/26 vs 6/33 for other cancers, p =0.025, OR=3.86 [1.19-12.47]). Two patients had a negative PET/CT (a colon cancer and a bladder cancer) and 2 patients, with positive PET/CT, had a benign colorectal tumor. PET/CT had a sensitivity of 94-100% for the diagnosis of cancer in this patient. Conclusions: Whole-body PET/CT confirmed the high incidence of cancer in patients with IE and could now be proposed in these cases.